2013
DOI: 10.1007/bf03346761
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of sexual dysfunction after transurethral resection of the prostate (TURP): A12 months follow-up

Abstract: The aim of this study was to evaluate the impact of risk factors of erectile dysfunction (ED) after transurethral resection of the prostate (TURP) in men with lower urinary tract symptoms caused by bladder outlet obstruction secondary to benign prostatic hyperplasia. The study was conducted prospectively on 178 consecutive patients (normal IIEF-5 before surgery, ≥ 22) who underwent TURP. Patients were assessed before surgery and at 12 months. At 12 months, the IIEF-5 score significantly decreased from24 to 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Besides these major premises, several community-based studies have recently confirmed the association between LUTS and ED [6][7][8]. Although severity of LUTS, assessed by the International Prostate Symptom Score (IPSS), significantly correlates with the prevalence of ED, the exact relationship between these two agedependent conditions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these major premises, several community-based studies have recently confirmed the association between LUTS and ED [6][7][8]. Although severity of LUTS, assessed by the International Prostate Symptom Score (IPSS), significantly correlates with the prevalence of ED, the exact relationship between these two agedependent conditions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…22 The important role of organic determinants and, in particular, CVD risk factors have been considered the most important pathogenic factors underlying ED 1 and our findings may be justified by previous observations where men with CVD and overall atherosclerotic cardiovascular events frequently experienced ED. [24][25][26][27] One of the major strengths of this study was to create a multivariable risk group stratification that could be helpful in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides age, LUTS and MetS also participate in a variety of other risk factors, such as obesity, hyperglycemia, hypertension, lack of androgen, depression, and smoking, consequently indicating that metabolic syndrome might have a major role in the pathogenesis of LUTS [11] A link between metabolic syndrome and prostate growth rate has also been found in clinical series [12,13] . All these findings point out that the MetSrelated BPH/ LUTS should be counted as potentially objective therapy in order to oppose the resulting prostate rapid growth [14] The objective of the present study was to evaluate the effects of MetS on the prostatic volume and LUTS/BPH in a sample of Iraqi men aged >50 years.…”
Section: Introductionmentioning
confidence: 96%